Plant Sciences: Macmillan Science Library - Robinson, Richard (Macmillan Reference USA, 2011)
For students, plants are the introduction to life sciences. This encyclopedia introduces the fundamentals -- such as cells, transportation and photosynthesis, and also examines related fields, such as agribusiness, conservation and ethnobotany. The set is fully illustrated and offers marginal definitions, timelines and sidebars throughout.